2016
DOI: 10.1101/gad.285692.116
|View full text |Cite
|
Sign up to set email alerts
|

Structural visualization of the p53/RNA polymerase II assembly

Abstract: The master tumor suppressor p53 activates transcription in response to various cellular stresses in part by facilitating recruitment of the transcription machinery to DNA. Recent studies have documented a direct yet poorly characterized interaction between p53 and RNA polymerase II (Pol II). Therefore, we dissected the human p53/Pol II interaction via single-particle cryo-electron microscopy, structural docking, and biochemical analyses. This study reveals that p53 binds Pol II via the Rpb1 and Rpb2 subunits, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 74 publications
(110 reference statements)
3
26
0
Order By: Relevance
“…S6. We suspect that p53's rapid removal could potentially lead to faster "repurposing" of the RE for additional rounds of p53-mediated recruitment of other basal transcription factors such as TFIIB (55,56), RNA polymerase II (32), and TFIIH (31,52,57). Stable prolonged binding of p53 to a TFIID/DNA complex can potentially negatively regulate PIC formation and squelch transcription.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S6. We suspect that p53's rapid removal could potentially lead to faster "repurposing" of the RE for additional rounds of p53-mediated recruitment of other basal transcription factors such as TFIIB (55,56), RNA polymerase II (32), and TFIIH (31,52,57). Stable prolonged binding of p53 to a TFIID/DNA complex can potentially negatively regulate PIC formation and squelch transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our single-molecule studies, EM structural analysis revealed that conversion of canonical TFIID to a rearranged DNA binding conformation is enhanced in the presence of p53 and DNA. TFIID/DNA binding induces p53 dissociation, which may potentially aid subsequent recruitment of p53 cocomplexes (e.g., p53/Mediator [30], p53/TFIIH [31], and p53/RNA polymerase II [32]) involved in PIC formation. Therefore, proper responses to divergent stress signals involve conserved structural mechanisms relating to p53's ability to dynamically stimulate TFIID's interaction with various target promoters.…”
mentioning
confidence: 99%
“…While p53 dissociates from the TFIID/DNA scaffold, it is highly likely that p53 will rapidly re-associate with the complex, particularly at the high concentrations (600nM) used in Supplementary Figure S6. We suspect that p53’s rapid removal could consequently lead to a faster “repurposing” of the RE for additional rounds of p53-mediated recruitment of other basal transcription factors such as TFIIB (51, 52), RNA Pol II (53), and TFIIH (49, 54, 55). In this scenario, stable prolonged binding of p53 to a TFIID/DNA complex would negatively regulate PIC formation, because p53 would occupy the RE and inhibit subsequent recruitment of a p53/basal factor co-complex.…”
Section: Discussionmentioning
confidence: 99%
“…Our cryo-EM studies further suggest that p53 aids in TFIID's transition to the rearranged DNA-binding conformation. 7 More recently, armed with significant advancement of cryo-EM, we have captured the first 3D structure of wild-type p53 bound to human Pol II 13 (Fig. 1).…”
Section: Capturing P53-mediated Transcription Assemblies Via Cryo-emmentioning
confidence: 99%
“…6,7 p53 was shown to bind several PIC components (i.e., TFIIB, TFIID, TFIIH, Mediator, Pol II) and subsequently aid their recruitment to the core promoter. [6][7][8][9][10][11][12][13] Thus, the interactions of p53 with multiple components of the PIC are crucial for transcription initiation. Researchers have studied stimulation of eukaryotic transcription by activators (e.g., p53) for the last 30 years.…”
Section: Introductionmentioning
confidence: 99%